Primary succession of microbial communities in an aquifer from the Covey Hill formation in Quebec, Canada - Beauregard-Tousignant, Samuel; Lazar, Cassandre Sara (Frontiers in Microbiology, 2025)
Aquifers in the continental subsurface have long been exploited for their resources. However, given the technical difficulties in accessing recurring subsurface samples, their community diversity and temporal dynamics remain largely misunderstood. Here, we investigated the effects of time and organic and inorganic carbon concentration variation on primary succession of microbial communities belonging to the Bacteria and Eukaryote domains colonizing rock surfaces and groundwater from a shallow fractured sandstone aquifer with a very high concentration of organic carbon and low concentration of nitrogen compounds. We attempted to recreate its physicochemical environment in a triplicate bioreactor setup and let the communities grow for 24 days. The sessile and planktonic communities were sampled daily in independent experiments and identified based on their 16S (Bacteria) or 18S (Eukaryote) rRNA genes. Time was the parameter with the strongest correlation both with alpha and beta diversity. The primary succession of all communities seems to have been divided into two temporal phases: in the first phase, approximately the two 1st days, the variations in community composition and diversity were high. In the second phase, the variation is more progressive and lasted until the end of the experiment. As expected in an aquifer rich in organic carbon, bacteria were mostly heterotrophs, except in the first few days where there were some chemolithotrophs, and eukaryotes were heterotrophs or likely mixotrophs. Unexpectedly, the alpha diversity of the sessile and planktonic communities varied following similar patterns, but the planktonic ones varied with a wider amplitude. Regarding carbon's effect, organic and inorganic carbon concentration variation explained a much smaller proportion of the variation in alpha and beta diversity than expected. We believe this is due to its high concentration throughout the incubation and to the strong limiting effect of other factors such as nitrogen concentration and pH. The communities of both Bacteria and Eukaryotes were more active than expected and their temporal dynamics and interactions should be further investigated in varying carbon, nitrogen and other nutrient concentrations to better understand how different perturbations can affect subsurface communities and, subsequently, us.